Health promotion actions and maternal near miss: an integrative review - Lívia Mara de Araújo; Maria Evilene Macena de Almeida; Ana Kelve de Castro Damasceno; Camila Teixeira Moreira Vasconcelos; Régia Christina Moura Barbosa Castro (Universidade Federal do Ceará, 2021)
Objective: to identify health promotion actions to reduce maternal near misses. Methods: this is an integrative review of the literature. The search for the articles was carried out in the MEDLINE/PubMed, CINAHL, LILACS, SCOPUS, and Web of Science databases, using the following combination: Near Miss, Healthcare AND Health promotion AND Maternal Welfare OR Maternal Health. Results: the 17 studies selected addressed the following recommendations on health promotion actions to decrease maternal near miss: enhancing prenatal care; access to reproductive planning; guidance and preparation for childbirth; education as an inclusion policy; continuing education for professionals and improvement of the regulation system. Conclusion: health promotion actions were evidenced in the study: carrying out effective prenatal care and actions related to management concerning professional training, adequate physical support in health units, and an organized and effective care network.